Pengaruh Service Convenience terhadap Loyalitas melalui Kepuasan Pelanggan Kereta Api di Wilayah Kota Malang - Desi Rahma Putri Pratiwi; Endi Sarwoko Sarwoko; Iva Nurdiana Nurfarida (Jurnal Riset Mahasiswa Manajemen, 2018)
The purpose of this study was to determine the effect of service convenience to Loyalty by means of customer satisfaction on KA. This type of research is survey using hypothesis testing with a quantitative approach. The sampling technique in this study was using accidental sampling with total sample amounted to 110 customers KA. Analysis of the data used ispath analysis. The result of this direct effect of service convenience on loyalty and the indirect effect of service convenience on loyalty through customer satisfaction.